2009
DOI: 10.1007/s10151-009-0457-7
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of anastomotic leaks after colectomy

Abstract: The earliest clinical predictors of an anastomotic leak are pulmonary and/or neurological. Awareness of these findings might help in early diagnosis and treatment of an anastomotic leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 18 publications
7
50
1
8
Order By: Relevance
“…The AL rate after colorectal surgery varies between 1% and 40%, depending on the definition of leakage and on the type of resection performed, being higher in extraperitoneal anastomosis (Bellows et al, 2009). The rate of 7.6% in this study falls within the range of previously published series.…”
Section: Discussionmentioning
confidence: 99%
“…The AL rate after colorectal surgery varies between 1% and 40%, depending on the definition of leakage and on the type of resection performed, being higher in extraperitoneal anastomosis (Bellows et al, 2009). The rate of 7.6% in this study falls within the range of previously published series.…”
Section: Discussionmentioning
confidence: 99%
“…4 With current screening and diagnostic methods, the interval between construction of the colorectal anastomosis and diagnosis of leakage varies between 6 and 13 days. [5][6][7] Several studies have suggested that delay of diagnosis of CAL is associated with higher mortality rates and that only early management improves clinical outcome. [8][9][10] Therefore, new screening methods allowing detection of CAL in the early postoperative phase are needed.…”
mentioning
confidence: 99%
“…The AL rate after colorectal surgery varies between on the type of resection performed, being higher in extraperitoneal anastomosis (Bellows et al, 2009). The rate of 7.6% in this study falls within the range of previously published series.…”
Section: Discussionmentioning
confidence: 99%